Ag-plated material, manufacturing method for Ag-plated material, and electrical parts
Patent Information
- Application Number
- JP2020214110
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-23
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2040-12-23
AI Technical Summary
【0026】 本発明によれば、優れた耐摩耗性を備えるAgめっき材を提供できる。
Smart Images

Figure 0007644597000002 
Figure 0007644597000003 
Figure 0007644597000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an Ag-plated product, a method for producing an Ag-plated product, and an electrical component. [Background technology]
[0002] Conventionally, silver (Ag) plated materials have been used as materials for sliding contact parts such as switches, connectors, and terminals used in automobiles to prevent oxidation of conductive materials such as copper and copper alloys due to heating during the sliding process.
[0003] Patent Document 1 describes a plated article in which a multilayer plating film is formed on a substrate made of a conductive metal, the plated article having, in that order, a porous plating layer mainly composed of Ni or Cu and a surface plating layer mainly composed of Au or Ag on the substrate, with a large number of holes formed on the surface of the multilayer plating film (Claim 1).
[0004] Patent Document 1 discloses the following as the reason for forming a large number of holes on the surface of the multilayer plating film (
[0020] ):
[0005] That is, by forming a surface plating layer on the porous plating layer, the surface plating layer is formed so as to follow the unevenness of the porous plating layer, and holes are also formed in the surface plating layer. The surface plating layer is easily formed on the convex parts of the surface of the porous plating layer, and the surface plating layer is difficult to form on the bottom and side surfaces of the holes formed on the surface of the porous plating layer. As a result, there are areas where the surface plating layer is not formed or where the thickness of the surface plating layer is thin. The unevenness of the surface plating layer mainly composed of Au or Ag can prevent the concentration of corrosion current that causes galvanic corrosion, and rather improves corrosion resistance.
[0006] Patent Document 2 describes that the plating film described in Patent Document 1 has a large number of pores on its surface, and that the pores are filled with lubricating particles by a blasting treatment to provide the film with sliding properties (abstract).
[0007] Patent Document 3 describes an electrical contact material for connectors that has excellent abrasion resistance and can maintain good electrical connectivity for a long period of time even when the connector is repeatedly inserted and removed, and that has a substrate made of a metal material, a porous metal layer having a large number of pores provided on the substrate, and a filling portion that fills the pores in the porous metal layer, the filling portion being made of a metal material that is lower in hardness than the metal material that constitutes the porous metal layer (Abstract, Claim 1).
[0008] Patent documents 4 and 5 describe a method of providing a silver-plated product having excellent wear resistance by forming a surface layer made of silver on the surface of a base layer made of nickel formed on a base material, and also describe a method of improving the productivity of the silver-plated product by roughening the surface of the base material and forming a base layer made of nickel on the roughened surface of the base material, or by forming a base layer made of nickel on the base material, roughening the surface of the base layer, and then forming a surface layer made of silver on the surface of the base layer (both are abstracts, claim 1). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] WO2013 / 094766 Brochure [Patent Document 2] JP 2013-129902 A [Patent Document 3] JP 2015-59260 A [Patent Document 4] JP 2017-14588 A [Patent Document 5] JP 2017-14589 A Summary of the Invention [Problem to be solved by the invention]
[0010] In recent years, the need for electric vehicles such as EVs and PHVs has been increasing due to environmental regulations. Silver-plated drawn copper materials are often used for electric vehicles from the viewpoint of electrical conductivity and contact reliability. The characteristics required for such high-voltage terminals include insertion / removal resistance and abrasion resistance (collectively referred to as abrasion resistance in this specification), and preferably the ability to withstand micro-sliding abrasion (vibration resistance).
[0011] An object of the present invention is to provide an Ag-plated product having excellent abrasion resistance. [Means for solving the problem]
[0012] The first aspect of the present invention is An Ag-plated material having an Ag plating layer formed on a substrate made of a conductive metal, The Ag-plated material has a two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order formed on the substrate, the two-layer plating structure being provided in multiple layers from the substrate side.
[0013] A second aspect of the present invention is the method according to the first aspect, A base Ni plating layer is further formed between the two-layer plating structure closest to the substrate and the substrate.
[0014] A third aspect of the present invention is the method according to the second aspect, The thickness of the Ni plating layer is 0.05 to 2 μm.
[0015] A fourth aspect of the present invention is the aspect according to any one of the first to third aspects, A large number of pores are formed on the surface of the Ag-plated material.
[0016] A fifth aspect of the present invention is the fourth aspect, The density of the holes is 5000 to 100,000 holes / mm 2 It is.
[0017] A sixth aspect of the present invention is the fourth or fifth aspect, The average diameter of the pores is 1 to 3 0 μm.
[0018] A seventh aspect of the present invention is an aspect according to any one of the first to sixth aspects, The porous Ni plating layer has a thickness of 0.1 to 3 μm.
[0019] An eighth aspect of the present invention is the aspect according to any one of the first to seventh aspects, The Ag plating layer has a thickness of 0.1 to 3 μm.
[0020] A ninth aspect of the present invention is a method for producing a composition comprising the steps of: A method for producing an Ag-plated product in which an Ag-plated layer is formed on a substrate made of a conductive metal, comprising the steps of: This is a method for producing an Ag-plated product, in which a two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order is formed on the substrate from the substrate side, and a plurality of such two-layer plating structures are formed.
[0021] A tenth aspect of the present invention is the ninth aspect, A base Ni plating layer is further formed between the two-layer plating structure closest to the substrate and the substrate.
[0022] An eleventh aspect of the present invention is the tenth aspect, The thickness of the Ni undercoat plating layer is set to 0.05 to 2 μm.
[0023] A twelfth aspect of the present invention is the aspect according to any one of the ninth to eleventh aspects, The thickness of the porous Ni plating layer is set to 0.1 to 3 μm.
[0024] A thirteenth aspect of the present invention is the aspect according to any one of the ninth to twelfth aspects, The Ag plating layer has a thickness of 0.1 to 3 μm.
[0025] A fourteenth aspect of the present invention is a method for producing a composition comprising the steps of: The present invention relates to an electrical component, which is a contact or terminal component, using the Ag-plated product according to any one of the first to eighth aspects as a material. Effect of the Invention
[0026] According to the present invention, it is possible to provide an Ag-plated product with excellent abrasion resistance. [Brief description of the drawings]
[0027] [Figure 1] 1 is a secondary electron image (2000x) of the surface of the Ag-plated product of Example 1 taken with a SEM (scanning electron microscope). [Diagram 2] 1 is a SIM (scanning ion microscope) image of a cross section of the Ag-plated product of Example 1. [Diagram 3] 1 is a SIM image of a cross section of the Ag-plated product of Example 5. [Figure 4] 1 is a secondary electron image (magnification 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 2. [Diagram 5] 1 is a secondary electron image (magnification 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 3. [Figure 6] 1 is a secondary electron image (magnification 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 4. [Figure 7] 1 is a secondary electron image (magnification 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 6. [Figure 8] 1 is a SIM image of a cross section of the Ag-plated product of Comparative Example 7. [Figure 9](a) is a secondary electron image (2000 times magnification) of the surface of the Ag plating material of Example 1 by EPMA (electron probe microanalyzer). (b) is a backscattered electron composite image (2000 times magnification) of the surface of the Ag plating material by EPMA (electron probe microanalyzer). (c) is a characteristic X-ray image of Ag by WDX (wavelength dispersive X-ray spectroscopy) of the surface of the Ag plating material by EPMA (electron probe microanalyzer). (d) is a characteristic X-ray image of Ni by WDX (wavelength dispersive X-ray spectroscopy) of the surface of the Ag plating material by EPMA (electron probe microanalyzer). [Figure 10] (a) is a secondary electron image (2000 times magnification) of the surface of the Ag plating material of Example 1 after the abrasion resistance test by EPMA (electron probe microanalyzer). (b) is a backscattered electron composite image (2000 times magnification) of the surface of the Ag plating material after the abrasion resistance test by EPMA (electron probe microanalyzer). (c) is a characteristic X-ray image of Ag by WDX (wavelength dispersive X-ray spectroscopy) of the surface of the Ag plating material after the abrasion resistance test by EPMA (electron probe microanalyzer). (d) is a characteristic X-ray image of Ni by WDX (wavelength dispersive X-ray spectroscopy) of the surface of the Ag plating material after the abrasion resistance test by EPMA (electron probe microanalyzer). [Figure 11] It is a diagram for explaining the method of calculating the plating film thickness.
Mode for Carrying Out the Invention
[0028] Hereinafter, this embodiment will be described. In this specification, "~" refers to a value that is equal to or greater than a predetermined value and equal to or less than a predetermined value.
[0029] <Ag plating material> The Ag plating material according to this embodiment is an Ag plating material in which an Ag plating layer is formed on a base material made of a conductive metal, and on the base material, from the base material side (lower side), a porous Ni (nickel) plating layer and an Ag (silver) plating layer are formed in this order. It is characterized by having a two-layer plating structure and including a plurality of such two-layer plating structures.
[0030] The substrate may be made of any conductive metal, including copper or a copper alloy.
[0031] The porous Ni plating layer is, as its name suggests, a porous plating layer.
[0032] The porous Ni plating layer is a porous Ni plating film having a three-dimensional structure that can be produced, for example, by a known porous Ni plating solution and electrolytic plating method, and has pores with diameters of approximately 1 μm to several tens of μm when observed from the surface, and has a high specific surface area.
[0033] The porous Ni plating layer is a plating layer mainly composed of Ni, and may contain other elements such as P, B, Co, Fe, Cr, Cu, Zn, etc., within the scope of the effects of the present invention. Hereinafter, the Ni plating layer and the Ag plating layer mean that Ni and Ag are the main components, respectively.
[0034] A specific Ni content in the porous Ni plating layer is, for example, 90 mass % or more, preferably 95 mass % or more, and may further be 99 mass % or more.
[0035] The thickness of the porous Ni plating layer is preferably 0.1 to 3 μm. With this thickness, the Ni plating layer can be made porous with the number density and average diameter of the pores appropriately set. The thickness of the porous Ni plating layer is more preferably 0.3 to 2 μm, and further preferably 0.8 μm or more.
[0036] The Ag plating layer may be an Ag plating film obtained by applying Ag strike plating and then Ag plating (main plating), and is a plating layer containing Ag as a main component. The Ag plating layer may contain other elements, such as C, N, S, Se, Sb, Co, Cu, Au, In, P, Zn, Sn, Pd, Bi, etc., within the range in which the effects of the present invention are achieved. For convenience, in order to distinguish between the Ag strike plating and the Ag plating layer formed thereon, the Ag plating layer formed on the Ag strike plating layer may be referred to as the Ag main plating layer in this specification.
[0037] The specific Ag content in the Ag plating layer is, for example, 90 mass % or more, preferably 95 mass % or more, and may further be 99 mass % or more from the viewpoint of electrical conductivity.
[0038] It is preferable that a large number of holes are formed on the surface of the Ag-plated material. In other words, it is preferable that a large number of holes are observed on the most surface side (exposed surface) of the multiple Ag-plated layers. Also, a large number of holes may be observed on the upper surface of any of the Ag-plated layers constituting the Ag-plated material. It is considered that the holes in the Ag-plated layer are observed because the Ag-plated layer covers the surface of the porous Ni-plated layer formed underneath, and the Ag-plated layer is not covered until the holes in the porous Ni-plated layer are completely filled.
[0039] From the substrate side, a two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order (alternately overlapping) is formed, and the presence of a plurality of these two-layer plating structures can be confirmed by observing the cross section with an electron microscope. For example, FIG. 2 is a SIM image (scanning ion microscope image) obtained by observing the cross section of the Ag-plated material of the present invention (Example 1) with an SIM (scanning ion microscope). From FIG. 2, it can be confirmed that a two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order is formed, and that a plurality of these two-layer plating structures (three in FIG. 2) are provided. It is more preferable that the two-layer plating structure has three or more. The porous Ni plating layer is a light gray layer, and the Ag plating layer is dark gray. Irregularities (holes) are observed in the porous Ni plating layer, and Ag plating is formed on the surface.
[0040] The number density and size of holes on the surface of the Ag-plated material were also evaluated. Using a laser microscope VK-X150 manufactured by Keyence Corporation, shape measurements were performed using an objective lens of ×100, and volume and area measurements were performed using a multi-file analysis application, with the analysis range set to 100 μm × 100 μm. The height with the largest area detected was set as the reference (height 0) (calculated by the analysis application), and the part where no object (plating surface) was detected at a distance (position) of 0.5 μm from the reference height in the depth direction of the Ag-plated layer was considered to be a hole (porous part), and the number and area of the hole were measured. The number density of holes per unit area and the average diameter of the holes were then calculated. Holes with a diameter of less than 1 μm were excluded from the measurement.
[0041] In addition, a large number of holes (concavities and recesses) are formed on the upper surface of the Ag plating layer (the surface side of the Ag plating material) other than the outermost layer that constitutes the Ag plating material, and a porous Ni plating layer is formed on the upper surface of the Ag plating layer.
[0042] The density of the holes on the surface of the Ag-plated material is 5,000 to 100,000 holes / mm 2 It is preferable that:
[0043] The average diameter of the pores is preferably from 1 to 30 μm, and more preferably from 2 to 20 μm.
[0044] The thickness of the Ag plating layer is preferably 0.1 to 3 μm, more preferably 0.2 to 2 μm. At this thickness, a large number of holes can be formed in the Ag plating layer after appropriately setting the number density of the holes and the average diameter of the holes. If the thickness is more than 3 μm, there is a risk that the holes on the surface of the porous Ni plating layer may not be sufficiently formed on the surface because the holes are filled with the Ag plating layer. However, the above numerical range is only an example. Ultimately, the thickness of the Ag plating layer may be any thickness as long as a large number of holes are formed on the upper surface of the Ag plating layer. It is more preferable that the thickness of any Ag plating layer constituting the Ag plating material is a thickness at which a large number of holes are formed on the upper surface of the Ag plating layer. Specifically, it is more preferably 0.2 to 2 μm, and even more preferably 0.5 μm or more.
[0045] In this embodiment, a plurality of two-layer plating structures are provided, each of which is a combination of a porous Ni plating layer and an Ag plating layer formed directly thereon. With this configuration, the Ag plating material of this embodiment has excellent wear resistance and preferably excellent vibration resistance.
[0046] It is preferable that an underlying Ni plating layer is further formed between the two-layer plating structure closest to the substrate side and the substrate. In particular, it is preferable to form an underlying Ni plating layer directly on the substrate and a porous Ni plating layer directly on the underlying Ni plating layer.
[0047] By forming the underlying Ni plating layer, when the Ag plating material is heated, for example, elements such as Cu and Fe, which are components of the substrate, can be prevented from diffusing into the Ag plating layer, and deterioration of characteristics such as deterioration of the adhesion between the substrate and the porous Ni plating layer can be suppressed.
[0048] If good adhesion can be ensured between the substrate (or the layer if any layer is formed on the substrate) and the porous Ni plating layer, there is no limitation on the underlying Ni plating layer. From the viewpoints of good adhesion and bendability, the thickness of the underlying Ni plating layer is preferably 0.05 to 2 μm.
[0049] <Manufacturing method of Ag plating material> As a method for manufacturing an Ag plating material according to this embodiment, it is a method for manufacturing an Ag plating material in which an Ag plating layer is formed on a substrate made of a conductive metal. On the substrate, a two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order is formed from the substrate side, and a plurality of such two-layer plating structures are formed. The content not described below shall be the same as the content described in the item <Ag plating material>.
[0050] (Step 1: Pretreatment step) As pretreatment, it is preferable to perform electrolytic degreasing and pickling on the substrate. For example, it is preferable to perform electrolytic degreasing with the substrate as the cathode and a separately prepared SUS plate as the anode to remove organic substances on the substrate. Then, it is preferable to pickle the substrate with an aqueous solution containing an acid such as sulfuric acid.
[0051] (Step 2: Underlayer Ni plating layer formation step) Next, it is preferable to form an underlayer Ni plating layer. There are no limitations on the composition (constitution) and plating conditions of the plating bath when forming the underlayer Ni plating layer, and the plating baths (sulfamic acid bath; composed of nickel sulfamate, boric acid, nickel chloride, etc.) and plating conditions listed in the examples described later can be used. Other plating baths include Watts bath (composed of nickel sulfate, nickel chloride, boric acid, etc.) and all-chloride bath (composed of nickel chloride, boric acid, etc.).
[0052] The Ni concentration in this underlayer Ni plating solution is preferably 5 to 200 g / L, more preferably 10 to 180 g / L, and most preferably 20 to 150 g / L. It is preferable to perform electroplating using such a plating solution.
[0053] The liquid temperature of the plating solution when forming the underlayer Ni plating layer is preferably 10 to 70 °C, more preferably 25 to 55 °C. The current density is preferably 15 A / dm 2 or less, more preferably 10 A / dm 2 or less, and still more preferably 0.5 to 7 A / dm 2 is.
[0054] (Step 3: Porous Ni plating layer formation step) It is preferable to form a porous Ni plating layer directly on the base Ni plating layer. There are no limitations on the constitution (composition) of the plating bath (liquid) and plating conditions when forming the porous Ni plating layer, as long as plating is performed in a plating bath containing Ni ions and a porous plating layer containing Ni as a main component is formed.
[0055] Specifically, an example of the method is electroplating in a plating bath containing Ni ions and a water-soluble quaternary ammonium salt having a hydrophobic group. The quaternary ammonium salt can be added to a known Ni electroplating bath.
[0056] Examples of known electroplating baths include a Watts bath, a nickel sulfamate bath, and a nickel organic acid bath.
[0057] The Ni concentration in this porous Ni plating solution is preferably 5 to 200 g / L, more preferably 10 to 180 g / L, and most preferably 20 to 150 g / L.
[0058] The temperature of the plating solution when forming the porous Ni plating layer is preferably 10 to 70° C., more preferably 25 to 55° C. The current density is preferably 15 A / dm 2 More preferably, it is 10 A / dm or less. 2 Less than 0.5 to 7 A / dm 2 It is.
[0059] (Step 4: Ag strike plating layer formation step) It is preferable to form an Ag strike plating layer directly on the porous Ni plating layer. The composition of the plating bath and plating conditions when forming the Ag strike plating layer are not limited, and known plating baths and plating conditions can be applied. In addition, the plating baths and plating conditions described in the Examples section below can be used.
[0060] The Ag concentration in this Ag strike plating solution is preferably 0.01 to 15 g / L, more preferably 0.1 to 10 g / L, and most preferably 0.2 to 5 g / L. It is also preferable to perform Ag strike plating by electroplating.
[0061] The temperature of the plating solution when forming the Ag strike plating layer is preferably 10 to 60° C., more preferably 15 to 55° C. The current density is preferably 8 A / dm 2 More preferably, 5 A / dm 2 Less than 0.2 to 3 A / dm 2 It is.
[0062] (Step 5: Ag plating layer formation step) It is preferable to form a main Ag plating layer directly on the Ag strike plating layer. There is no limitation on the composition of the plating bath and plating conditions when forming the main Ag plating layer, and the plating bath and plating conditions listed in the Examples section below can be used. The thickness of the main Ag plating layer can be set to a thickness that allows a large number of holes to be formed in the main Ag plating layer, and it is preferable to form it by electroplating.
[0063] The Ag concentration in this main Ag plating solution is preferably 5 to 200 g / L, more preferably 20 to 180 g / L, and most preferably 50 to 150 g / L.
[0064] The temperature of the plating solution when forming the main Ag plating layer is preferably 10 to 60° C., more preferably 15 to 55° C. The current density is preferably 15 A / dm 2 More preferably, it is 10 A / dm or less. 2 Less than 0.5 to 7 A / dm 2 It is.
[0065] The Ag strike plating layer and the main Ag plating layer formed on the Ag strike plating layer are considered to be one Ag plating layer, since, for example, even when observing the cross section of an Ag-plated product under a microscope, the Ag strike plating layer is very thin and its composition is Ag, making it difficult to distinguish them.
[0066] Next, the set of (Step 3) to (Step 5) is repeated. Then, a desired number (plurality) of two-layer plating structures are formed. After that, the structure is appropriately washed with water to obtain an Ag-plated material.
[0067] When the Ag-plated material of this embodiment is used as a material to manufacture electrical components such as switches, connectors, contacts, or terminal components, the electronic components have excellent abrasion resistance and vibration resistance.
[0068] The technical scope of the present invention is not limited to the above-described embodiments, but also includes forms in which various modifications and improvements are made within the scope that can derive specific effects obtained by the constituent elements of the invention and their combinations. EXAMPLES
[0069] The present invention will now be described in detail with reference to examples. The present invention is not limited to the following examples. Note that the contents not described below are the same as those described in the present embodiment.
[0070] [Example 1] (Step 1: Pretreatment (electrolytic degreasing and pickling)) First, a pure copper metal plate (C1020) measuring 67 mm x 50 mm x 0.3 mm was prepared as the substrate, and this substrate and a separately prepared SUS plate were placed in an alkaline degreasing solution, and electrolytic degreasing was performed for 30 seconds at a voltage of 5 V, with the substrate as the cathode and the SUS plate as the anode. The substrate was then pickled in a 3% sulfuric acid aqueous solution for 15 seconds. Between each step, a 15-second water rinse was performed.
[0071] (Step 2: Formation of the Ni plating layer) Next, a plating solution (bath) was prepared, which was an aqueous solution containing 540 g / L of nickel sulfamate tetrahydrate, 25 g / L of nickel chloride, and 35 g / L of boric acid. In the plating solution, the substrate was used as the cathode and a separately prepared SK (sulfur-containing) nickel electrode plate was used as the anode, and the plating solution was stirred at 500 rpm with a magnetic stirrer while a current density of 7 A / dm 2Electroplating was performed at a solution temperature of 50°C to form a 0.2 µm thick undercoat Ni plating layer directly on the substrate.
[0072] (Step 3: Formation of porous Ni plating layer) Next, a plating solution was prepared, which consisted of an aqueous solution containing 540 g / L of nickel sulfamate tetrahydrate, 25 g / L of nickel chloride, 35 g / L of boric acid, and 10 mL / L of Top Porous Nickel RSN (manufactured by Okuno Chemical Industries Co., Ltd.) as a nickel plating additive that produces a nickel plating film with a porous structure. The total volume of the plating solution was 1 L.
[0073] During the plating, the substrate on which the undercoat Ni plating layer was formed (hereinafter, the intermediate product is referred to as the "substrate to be plated") was used as the cathode, and the SK nickel electrode plate was used as the anode. While stirring at 500 rpm with a magnetic stirrer, a current density of 1 A / dm was applied so that a volume of Ni equivalent to a non-porous Ni plating layer with a thickness of 1 μm (set value) was formed. 2 Electroplating was performed for 500 seconds at a solution temperature of 50° C. to form a porous Ni plating layer directly on the base Ni plating layer. The thickness of the porous Ni plating layer at this time (the above set value) is shown in Table 1 below.
[0074] For the material after the formation of the porous Ni plating layer, a fluorescent X-ray film thickness gauge (FT-110A manufactured by Hitachi High-Tech Science Corporation) was used to measure the thickness of the Ni plating layer at the center of the sample with a collimator diameter of φ0.2 mm and a measurement time of 10 seconds, resulting in a measurement of 1.2 μm, confirming that the film thickness was formed as set. Note that, based on the measurement principle of the fluorescent X-ray film thickness gauge, it is believed that the sum of the thicknesses of the base Ni plating layer and the porous Ni plating layer is measured as the thickness of the Ni plating layer.
[0075] (Step 4: Formation of Ag strike plating layer) Next, a plating solution was prepared, which consisted of an aqueous solution containing 3 g / L of potassium silver cyanide and 90 g / L of potassium cyanide. In the plating solution, the material to be plated was used as the cathode and a platinum-coated titanium electrode plate was used as the anode, and electroplating was performed for 10 seconds at a solution temperature of 25°C and the current density shown in the table while stirring at 500 rpm with a magnetic stirrer, and then the material was washed with water for 15 seconds.
[0076] (Step 5: Formation of the main Ag plating layer) Next, a silver plating bath was prepared, which consisted of an aqueous solution containing 175 g / L of potassium silver cyanide, 95 g / L of potassium cyanide, and 6 mg / L of selenium. In the plating bath, the material to be plated was used as the cathode, and a silver electrode plate with a purity of 99.99% or more was used as the anode. While stirring at 500 rpm with a magnetic stirrer, the plating bath was heated at a current density of 0.5 A / dm2 so that a 1 μm thick (set value) Ag plating layer was formed. 2 Then, electroplating was performed at a solution temperature of 18°C for 240 seconds to form a main Ag plating layer directly on the Ag strike plating layer. The thickness of the Ag plating layer in Table 1 is the total thickness (above set value) of the Ag strike plating layer and the main Ag plating layer. After the formation of the main Ag plating layer, it was rinsed with water for 15 seconds.
[0077] After the Ag plating layer was formed on the material, a fluorescent X-ray thickness gauge (FT-110A, Hitachi High-Tech Science Corporation) was used to measure the thickness of the Ag plating layer at the center of the sample with a collimator diameter of φ0.2 mm and a measurement time of 10 sec. The result was 1 μm, confirming that the film thickness was formed as set.
[0078] Next, (Step 3) to (Step 5) (set) were repeated twice to produce an Ag-plated material consisting of a total of seven plating layers, including the base Ni plating layer (the Ag strike plating layer was counted as one layer together with the main Ag plating layer).
[0079] (Plating thickness) The thickness of each layer of the Ag-plated material was measured using an Auger electron spectrometer (JAMP-7800 Auger microprobe manufactured by JEOL Ltd.) at an acceleration voltage of 10 kV and a probe current of 1 × 10 -7Under the condition of A, beam diameter 100μmφ, the surface of the Ag-plated material was etched in the depth direction by Ar sputtering (accelerating voltage 3kV, emission current 25mA) while measuring Ag and Ni, and the plating thickness was calculated from the Ag and Ni depth profile. The measurement data step interval was 0.5 minutes between 0 and 300 seconds, 1 minute between 300 and 600 seconds, and 2 minutes for 600 seconds or more.
[0080] A measurement example is shown in Figure 11. The method for calculating the plating thickness is explained below.
[0081] In FIG. 11, the horizontal axis is the sputtering time and the vertical axis is the concentration (atomic percentage) of Ag and Ni in the depth direction profile (depth profile), and a moving average line is created by calculating a 10-section moving average of the measurement data.
[0082] The maximum and minimum values were plotted (not shown) for each moving average line (there were two maximum values and two minimum values for the Ag moving average line, and three maximum values and two minimum values for the Ni moving average line, excluding the outermost surface). Furthermore, the sum of the adjacent maximum and minimum values (in terms of concentration) for each of the Ag and Ni moving average lines was divided by 2 to obtain an intermediate value, which was then plotted on the line between the maximum and minimum values to obtain the midpoint (shown as a white circle in the figure).
[0083] In addition, in the moving average line of the Ag depth profile, the midpoint on the side where the sputtering time is shorter (the outermost surface side) than the minimum value closest to the surface is plotted on the moving average line (between the minimum value and the outermost surface) at a concentration equal to the midpoint plotted adjacent to the minimum value and on the side where the sputtering time is longer, and this is set as the midpoint.
[0084] In addition, in the moving average line of the Ag profile in the depth direction, the midpoint on the side where the sputtering time is longer (on the substrate side) than the maximum value closest to the substrate is plotted as the midpoint on the moving average line (between the maximum value and the substrate side) with the same concentration as the midpoint plotted adjacent to the maximum value and on the side where the sputtering time is shorter.
[0085] In the moving average line of the Ni depth profile, the midpoint on the side (the outermost surface side) where the sputtering time is shorter than the maximum value closest to the surface is plotted as the midpoint on the moving average line (between the maximum value and the outermost surface) that has the same concentration as the midpoint plotted on the side of the maximum value adjacent to the maximum value where the sputtering time is longer.
[0086] In the moving average line of the Ni depth profile, the midpoint on the side where the sputtering time is longer (on the substrate side) than the maximum value closest to the substrate is plotted as the midpoint on the moving average line (between the maximum value and the substrate side) with the same concentration as the midpoint plotted on the side where the sputtering time is shorter adjacent to the maximum value.
[0087] Then, adjacent midpoints of the moving average lines for Ag and Ni were connected with a line, and the length in the horizontal direction (sputtering time) of the section with the maximum value above this line was measured. This length was converted into a thickness using the SiO2 etching rate (etching speed 20 nm / min) to obtain the plating film thickness of each of the Ag plating layer and the Ni plating layer.
[0088] For the topmost Ag plating layer (shown as layer 7 in the figure), the thickness of the Ag plating layer was calculated using the above-mentioned etching rate, calculated from the length (time) on the horizontal axis from the topmost surface (where sputtering time is zero) to the midpoint closest to the topmost surface. The plating thickness defined in the claims of the present invention is calculated in this manner.
[0089] As a result, from the surface side of the Ag-plated material, the thickness of the Ag plating layer (7 layers) was 0.611 μm, the thickness of the porous Ni plating layer (6 layers) was 1.148 μm, the thickness of the Ag plating layer (5 layers) was 0.739 μm, the thickness of the porous Ni plating layer (4 layers) was 1.453 μm, the thickness of the Ag plating layer (3 layers) was 0.69 μm, and the thickness of the porous Ni plating layer (2 layers) was 1.099 μm.
[0090] (Wear resistance of Ag-plated materials) To evaluate the wear resistance of the silver-plated material, a precision sliding tester CRS-G2050-DWA model manufactured by Yamazaki Seiki Kenkyusho Co., Ltd. was used, and one side of the silver-plated material was processed into an embossed shape (hemispherical shape) with an inner diameter R = 1.5 mm, and brought into contact with the surface of the other silver-plated material (same flat plate shape) with a load of 5 N. The material was then slid back and forth at a sliding speed of 1.67 mm / sec and a sliding distance of 5 mm, and the number of times until the copper base was exposed was measured. However, if the contact resistance exceeded 1 mΩ, the product was deemed NG at that point.
[0091] As a result, the Ag-plated product of Example 1 had no exposure of the copper base even after 1,000 sliding cycles, and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0092] (Vibration resistance of Ag-plated material (fine wear resistance)) To evaluate the wear resistance of the silver-plated material thus produced, a precision sliding tester CRS-G2050-DWA model manufactured by Yamazaki Seiki Kenkyusho Co., Ltd. was used. One side of the silver-plated material was processed into an embossed shape (hemispherical shape) with an inner diameter R = 1.5 mm, and brought into contact with the surface of the other silver-plated material (same flat shape) with a load of 5 N. After that, the material was slid back and forth at a sliding speed of 0.2 mm / sec and a sliding distance of 0.1 mm, and the number of times until the contact resistance reached 1 mΩ or more was measured.
[0093] As a result, the Ag-plated product of Example 1 had a contact resistance of less than 1 mΩ even after 50,000 sliding cycles, and was excellent in vibration resistance.
[0094] (number density and average diameter of holes on the surface of Ag-plated material) The number density and average diameter of pores observed on the surface of the Ag-plated material were evaluated.
[0095] Using a laser microscope VK-X150 manufactured by Keyence Corporation, shape measurements were performed using an objective lens ×100, and volume and area measurements were performed using a multi-file analysis application, with the analysis range being 100 μm × 100 μm.
[0096] In the analysis range, the height at which the largest area was detected was taken as the surface (calculated by the analysis application), and the area where no object (plated surface) was detected at a distance (position) of 0.5 μm from the surface in the depth direction was considered to be a hole (porous area), and the number and area of the holes were measured. The average area of the holes was calculated from the number and area of the measured holes, and the diameter of a circle with the same area as this average area of the holes was calculated to determine the average diameter of the holes. The number density of holes per unit area was also calculated from the measurement results.
[0097] As a result, the hole density was 9,300 / mm 2 The average diameter of the pores was 16.3 μm.
[0098] The structure and evaluation results of the Ag-plated material in each example are shown in Table 1 below. [Table 1]
[0099] [Example 2] In Example 2, the composition of the Ni plating solution used for the porous Ni plating was an aqueous solution containing 540 g / L of nickel sulfamate tetrahydrate, 25 g / L of nickel chloride, 35 g / L of boric acid, and 8 mL / L of Top Porous Nickel RSN (manufactured by Okuno Chemical Industries Co., Ltd.) as a nickel plating additive that provides a nickel plating film with a porous structure. The composition of the Ag plating solution used for the main Ag plating was an aqueous solution containing 175 g / L of potassium silver cyanide, 95 g / L of potassium cyanide, and 55 mg / L of selenium. In the process of forming the main Ag plating layer, the plated material was used as the cathode and a silver electrode plate with a purity of 99.99% by mass or more was used as the anode, and the current density was set to 5 A / dm2 so that an Ag plating layer with a thickness of 1 μm was formed while stirring at 500 rpm with a stirrer. 2 An Ag-plated product was produced in the same manner as in Example 1, except that the solution temperature was set to 18° C. and electroplating was performed for 24 seconds to form a main Ag plating layer.
[0100] The plating thickness of this Ag-plated material was measured and calculated in the same manner as in the Examples. The results were, from the surface side of the Ag-plated material, that the Ag plating layer (7 layers) was 0.613 μm thick, the porous Ni plating layer (6 layers) was 0.998 μm thick, the Ag plating layer (5 layers) was 0.825 μm thick, the porous Ni plating layer (4 layers) was 1.384 μm thick, the Ag plating layer (3 layers) was 0.637 μm thick, and the porous Ni plating layer (2 layers) was 1.415 μm thick.
[0101] The wear resistance of this Ag-plated material was evaluated in the same manner as in Example 1. As a result, even after 1,000 sliding cycles, the copper base was not exposed and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0102] Furthermore, when the vibration resistance of the Ag-plated product was evaluated in the same manner as in Example 1, the contact resistance was less than 1 mΩ even after 50,000 sliding movements, demonstrating excellent vibration resistance.
[0103] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 10,800 pores / mm 2 , 16.2 μm.
[0104] [Example 3] An Ag-plated product was produced in the same manner as in Example 2, except that (a set of) (Step 3) to (Step 5) was repeated once to form a total of five layers.
[0105] The wear resistance of this Ag-plated material was evaluated in the same manner as in Example 1. As a result, even after 1,000 sliding cycles, the copper base was not exposed and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0106] In addition, the Ag-plated material was evaluated for vibration resistance in the same manner as in Example 1. As a result, the contact resistance was less than 1 mΩ even after 13,000 sliding cycles, demonstrating excellent vibration resistance (the contact resistance exceeded 1 mΩ after 20,000 sliding cycles).
[0107] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 25,500 pores / mm 2 , 7.1 μm.
[0108] [Example 4] An Ag-plated product was produced in the same manner as in Example 2, except that (a set of) (Step 3) to (Step 5) was repeated three times to form a total of nine layers.
[0109] The wear resistance of this Ag-plated material was evaluated in the same manner as in Example 1. As a result, even after 1,000 sliding cycles, the copper base was not exposed and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0110] Furthermore, when the vibration resistance was evaluated in the same manner as in Example 1, the contact resistance was less than 1 mΩ even after 50,000 sliding movements, demonstrating excellent vibration resistance.
[0111] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 23,100 pores / mm 2 , 7.7 μm.
[0112] [Example 5] An Ag-plated material was produced in the same manner as in Example 2, except that the electroplating time for the porous Ni plating was 250 seconds and the electroplating time for the main Ag plating was 12 seconds.
[0113] The plating thickness of this Ag-plated material was measured and calculated in the same manner as in the Examples. The results were, from the surface side of the Ag-plated material, that the Ag plating layer (7 layers) was 0.439 μm thick, the porous Ni plating layer (6 layers) was 0.425 μm thick, the Ag plating layer (5 layers) was 0.463 μm thick, the porous Ni plating layer (4 layers) was 0.561 μm thick, the Ag plating layer (3 layers) was 0.386 μm thick, and the porous Ni plating layer (2 layers) was 0.439 μm thick.
[0114] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, even after 400 sliding cycles, the copper base was not exposed and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0115] In addition, the Ag-plated material was evaluated for vibration resistance in the same manner as in Example 1. As a result, the contact resistance was less than 1 mΩ even after 20,000 sliding cycles, demonstrating excellent vibration resistance (the contact resistance exceeded 1 mΩ after 30,000 sliding cycles).
[0116] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 43,400 pores / mm 2 , 4.9 μm.
[0117] [Example 6] An Ag-plated material was produced in the same manner as in Example 4, except that the electroplating time for the porous Ni plating was 250 seconds and the electroplating time for the main Ag plating was 12 seconds.
[0118] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, even after 800 sliding cycles, the copper base was not exposed and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0119] Furthermore, the Ag-plated product was evaluated for vibration resistance in the same manner as in Example 1. As a result, the contact resistance was less than 1 mΩ even after 50,000 sliding movements, demonstrating excellent vibration resistance.
[0120] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 38,800 pores / mm 2 , 4.5 μm.
[0121] [Example 7] An Ag-plated material was produced in the same manner as in Example 3, except that the electroplating time for the porous Ni plating was 250 seconds and the electroplating time for the main Ag plating was 12 seconds.
[0122] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, even after 150 sliding cycles, the copper base was not exposed and the contact resistance was less than 1 mΩ, demonstrating excellent wear resistance.
[0123] In addition, the Ag-plated material was evaluated for vibration resistance in the same manner as in Example 1. As a result, the contact resistance was less than 1 mΩ even after 10,000 sliding cycles, demonstrating excellent vibration resistance (the contact resistance exceeded 1 mΩ after 15,000 sliding cycles).
[0124] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 36,600 pores / mm 2 , 6.0 μm.
[0125] [Comparative Example 1] In Comparative Example 1, an Ag-plated product was produced in the same manner as in Example 2, except that only one two-layer plating structure was used (a total of three layers without repeating steps 3 to 5).
[0126] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 100 sliding cycles, the copper base was exposed, and the wear resistance was insufficient.
[0127] Furthermore, when the Ag-plated material was evaluated for vibration resistance in the same manner as in Example 1, the contact resistance exceeded 1 mΩ after 5,000 sliding movements, and the vibration resistance was not sufficient.
[0128] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 18,800 pores / mm 2 , 9.0 μm.
[0129] [Comparative Example 2] An Ag-plated material was produced in the same manner as in Example 1, except that only one two-layer plating structure was used (a total of three layers without repeating steps 3 to 5) and the electroplating time for this Ag plating was 720 seconds.
[0130] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 100 sliding cycles, the copper base was exposed, and the wear resistance was insufficient.
[0131] Furthermore, when the Ag-plated product was evaluated for vibration resistance in the same manner as in Example 1, the contact resistance exceeded 1 mΩ after 2,000 sliding movements, and the vibration resistance was not sufficient.
[0132] In addition, the number density and average diameter of the pores on the surface of the Ag-plated product were evaluated in the same manner as in Example 1, and were found to be 12,400 pores / mm 2 , 9.4 μm.
[0133] [Comparative Example 3] An Ag-plated material was produced in the same manner as in Example 1, except that only one two-layer plating structure was used (a total of three layers without repeating steps 3 to 5) and the electroplating time for this Ag plating was 1,200 seconds.
[0134] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 100 sliding cycles, the copper base was exposed, and the wear resistance was insufficient.
[0135] Furthermore, when the Ag-plated product was evaluated for vibration resistance in the same manner as in Example 1, the contact resistance exceeded 1 mΩ after 5,000 sliding movements, and the vibration resistance was not sufficient.
[0136] In addition, when the number density of holes on the surface of the Ag-plated product was evaluated in the same manner as in Example 1, no holes were found (0 holes / mm 2 (It was.)
[0137] [Comparative Example 4] The current density during porous Ni plating was 3A / dm 2 The electroplating time was 165 seconds, and the current density during Ag strike plating was 2 A / dm 2An Ag-plated material was produced in the same manner as in Example 1, except that only one two-layer plating structure was used (a total of three layers without repeating steps 3 to 5), and the electroplating time for this Ag plating was 1,200 seconds.
[0138] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 100 sliding cycles, the copper base was exposed, and the wear resistance was insufficient.
[0139] In addition, when the number density of holes on the surface of the Ag-plated product was evaluated in the same manner as in Example 1, no holes were found (0 holes / mm 2 (It was.)
[0140] [Comparative Example 5] Current density when forming porous Ni plating: 5A / dm 2 An Ag-plated product was prepared in the same manner as in Comparative Example 4, except that the electroplating time was 100 seconds.
[0141] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 1,000 sliding cycles, the copper base was exposed and the wear resistance was insufficient.
[0142] In addition, when the number density of holes on the surface of the Ag-plated product was evaluated in the same manner as in Example 1, no holes were found (0 holes / mm 2 (It was.)
[0143] [Comparative Example 6] An Ag-plated material was produced in the same manner as in Example 1, except that only one two-layer plating structure was used (a total of three layers without repeating steps 3 to 5), and the electroplating time for the porous Ni plating was 1,500 seconds and the electroplating time for the main Ag plating was 720 seconds.
[0144] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, the contact resistance exceeded 1 mΩ after 100 sliding cycles, and the wear resistance was insufficient.
[0145] Furthermore, when the vibration resistance of this Ag-plated product was evaluated in the same manner as in Example 1, the contact resistance exceeded 1 mΩ after 3,000 sliding movements, and the vibration resistance was not sufficient.
[0146] In addition, the number density and average diameter of the pores on the surface of the Ag-plated material were evaluated in the same manner as in Example 1, and were found to be 4,600 pores / mm 2 , 31.2 μm.
[0147] [Comparative Example 7] In Comparative Example 7, no undercoat Ni plating was provided, and no additive (Top Porous Nickel RSN) was added to the Ni plating solution in step 3 of Example 1 (i.e., no porous Ni plating layer was provided), and a Ni plating layer having a thickness of 1 μm was formed, and the current density of Ag strike plating was set to 2 A / dm 2 An Ag-plated product was produced in the same manner as in Example 1, except that the above-mentioned conditions were met.
[0148] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 100 sliding cycles, the copper base was exposed, and the wear resistance was insufficient.
[0149] Furthermore, when the vibration resistance of this Ag-plated product was evaluated in the same manner as in Example 1, the contact resistance exceeded 1 mΩ after 5,000 sliding movements, and the vibration resistance was not sufficient.
[0150] In addition, when the number density of holes on the surface of the Ag-plated product was evaluated in the same manner as in Example 1, no holes were found (0 holes / mm 2 (It was.)
[0151] [Comparative Example 8] In Comparative Example 8, a Ni plating layer having a thickness of 1 μm was formed without providing a base Ni plating layer and without adding an additive (Top Porous Nickel RSN) to the Ni plating solution in step 3 of Example 1 (i.e., without providing a porous Ni plating layer), and Ag strike plating was performed on the Ni plating layer at a current density of 2 A / dm 2An Ag-plated product was produced in the same manner as in Example 2, except that the time for the main Ag plating was 120 seconds and only one Ag plating layer having a thickness of 5 μm was formed.
[0152] The wear resistance of this Ag-plated product was evaluated in the same manner as in Example 1. As a result, after 100 sliding cycles, the copper base was exposed, and the wear resistance was insufficient.
[0153] Furthermore, when the vibration resistance was evaluated in the same manner as in Example 1, the contact resistance exceeded 1 mΩ after 5,000 sliding movements, and the vibration resistance was not sufficient.
[0154] In addition, when the number density of holes on the surface of the Ag-plated product was evaluated in the same manner as in Example 1, no holes were found (0 holes / mm 2 (It was.)
[0155] FIG. 1 is a secondary electron image (2000x) of the surface of the Ag-plated product of Example 1 taken with a SEM (scanning electron microscope). FIG. 2 is a SIM (scanning ion microscope) image of a cross section of the Ag-plated product of Example 1. FIG. 3 is a SIM image of a cross section of the Ag-plated product of Example 5. FIG. 4 is a secondary electron image (2000x) taken by an SEM of the surface of the Ag-plated product of Comparative Example 2. FIG. 5 is a secondary electron image (magnification: 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 3. FIG. 6 is a secondary electron image (magnification: 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 4. FIG. 7 is a secondary electron image (magnification: 2000) taken by an SEM of the surface of the Ag-plated product of Comparative Example 6. FIG. 8 is a SIM image of a cross section of the Ag-plated product of Comparative Example 7. FIG. 9(a) is a secondary electron image (2000x) of the surface of the Ag-plated product of Example 1 taken with an EPMA (electron probe microanalyzer). FIG. 9(b) is a backscattered electron composition image (2000x) of the surface of the Ag-plated material taken with an EPMA (electron probe microanalyzer). Figure 9(c) is a characteristic X-ray image of Ag obtained by WDX (wavelength dispersive X-ray spectroscopy) using an EPMA (electron probe microanalyzer) on the surface of an Ag-plated material. Figure 9(d) is a characteristic X-ray image of Ni obtained by WDX (wavelength dispersive X-ray spectroscopy) using an EPMA (electron probe microanalyzer) on the surface of an Ag-plated material. FIG. 10(a) is a secondary electron image (2000x) of the surface of the Ag-plated material of Example 1 after the wear resistance test, taken with an EPMA (electron probe microanalyzer). FIG. 10(b) is a backscattered electron composition image (2000x) taken with an EPMA (electron probe microanalyzer) of the surface of the Ag-plated material after the wear resistance test. FIG. 10(c) is a characteristic X-ray image of Ag obtained by WDX (wavelength dispersive X-ray spectroscopy) using an EPMA (electron probe microanalyzer) on the surface of the Ag-plated material after the wear resistance test. FIG. 10(d) is a characteristic X-ray image of Ni obtained by WDX (wavelength dispersive X-ray spectroscopy) using an EPMA (electron probe microanalyzer) on the surface of the Ag-plated material after the wear resistance test.
[0156] As shown in FIG. 1, in Example 1, a large number of pores are formed on the surface of the Ag-plated product.
[0157] As shown in Fig. 2, in Example 1, a two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order is formed, and it can be confirmed that there are three sets of this two-layer plating structure. In addition, a large number of holes can be confirmed on the surface of the porous Ni plating layer other than the outermost surface side of the Ag-plated material, and it can be confirmed that each Ag plating layer provided directly on each porous Ni plating layer penetrates into the holes. This can also be confirmed in Fig. 3 showing a SIM image of the cross section of the Ag-plated material of Example 5.
[0158] As shown in Figure 9(c), Ag was confirmed in the white areas of the image in Figure 9(b), while Ni was observed in the black areas (i.e., holes formed in the Ag plating layer) in the image in Figure 9(b), as shown in Figure 9(d).
[0159] As shown in Figure 10(c) after the wear resistance test of the Ag-plated material, Ag was confirmed in the white parts of the image in Figure 10(b), and it is clear that the Ag plating remains. On the other hand, as shown in Figure 10(d) in the black parts of the image in Figure 10(b), a mesh-like area with a higher concentration of Ni was observed compared to Figure 9(d). It is believed that the sliding test caused parts of the soft Ag plating layer on the surface to be scraped off, exposing parts of the porous Ni plating layer, resulting in the mesh-like appearance observed.
[0160] As shown in Table 1, the examples had good wear resistance and vibration resistance, but the comparative examples did not achieve the same wear resistance and vibration resistance as the examples.
[0161] In the examples and comparative examples, the Ni purity of the Ni plating layer and the porous Ni plating layer was 99% by mass or more, and the Ag purity of the Ag strike plating layer and the main Ag plating layer was 99% by mass or more.
Claims
1. An Ag-plated material having an Ag plating layer formed on a substrate made of a conductive metal, A two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order is formed on the substrate from the substrate side, and the substrate includes a plurality of such two-layer plating structures; A large number of holes are formed on the surface of the Ag-plated material, The density of the holes is 5,000 to 100,000 holes / mm 2 ; The hole is defined as a portion of the Ag-plated material where no object is detected within a depth direction of 0.5 μm from the height of the largest area detected when the Ag-plated material is observed with a laser microscope.
2. 2. The Ag-plated product according to claim 1, further comprising an underlying Ni plating layer formed between the two-layer plating structure closest to the substrate and the substrate.
3. 3. The Ag-plated product according to claim 2, wherein the thickness of the underlying Ni plating layer is 0.05 to 2 μm.
4. The Ag-plated product according to any one of claims 1 to 3, wherein the average diameter of the pores is 1 to 30 µm.
5. The Ag-plated product according to any one of claims 1 to 4, wherein the porous Ni plating layer has a thickness of 0.1 to 3 µm.
6. The Ag-plated product according to any one of claims 1 to 5, wherein the Ag plating layer has a thickness of 0.1 to 3 µm.
7. A method for producing an Ag-plated product in which an Ag plating layer is formed on a substrate made of a conductive metal, comprising the steps of: A two-layer plating structure having a porous Ni plating layer and an Ag plating layer in this order is formed on the substrate from the substrate side, and a plurality of such two-layer plating structures are formed; forming a large number of holes in the surface of the Ag-plated product with a density of 5,000 to 100,000 holes / mm2; This is a manufacturing method for Ag-plated products, in which the hole is defined as the area where no object is detected within a depth direction of 0.5 μm from the height where the largest area is detected when the Ag-plated product is observed with a laser microscope.
8. 8. The method for producing an Ag-plated product according to claim 7, further comprising forming an undercoat Ni plating layer between the two-layer plating structure closest to the substrate and the substrate.
9. The method for producing an Ag-plated product according to claim 8, wherein the thickness of the underlying Ni plating layer is 0.05 to 2 μm.
10. The method for producing an Ag-plated product according to any one of claims 7 to 9, wherein the porous Ni plating layer has a thickness of 0.1 to 3 µm.
11. The method for producing an Ag-plated product according to any one of claims 7 to 10, wherein the Ag plating layer has a thickness of 0.1 to 3 µm.
12. An electrical part which is a contact or terminal part using the Ag-plated product according to any one of claims 1 to 6 as a material.
Citation Information
Patent Citations
Process for making Ni-Cu-Ag multilayer film
CN1966779A
Plated product and method for producing the same
JP2013129902A
Electrical contact material for connector and production method thereof
JP2015059260A
Silver plated material and manufacturing method thereof
JP2017014588A
Silver plated material and manufacturing method thereof
JP2017014589A